Consent to intercourse and the transmission of veneral or serious diseases: a comparative overview - Mohamad Yunus, Mohamad Ismail (The Malaysian Current Law Journal Sdn Bhd, 2003)
The Law Commission Consultation Paper No. 139 invites views on how the law should deal with the obtaining of consent through the non-disclosure of material facts. What should a man be required to disclose to a woman before taking advantage of her consent to intercourse? Should any sexually transmissible disease or illness qualify for this purpose? What if the man suspects he might have a disease, but does not know for sure?